Immunological and inflammatory changes after simplifying to dual therapy in virologically suppressed HIV-infected patients through week 96 in a randomized trial. (August 2022) - Trujillo-Rodríguez, María; Muñoz-Muela, Esperanza; Serna-Gallego, Ana; Milanés-Guisado, Yusnelkis; Praena-Fernández, Juan Manuel; Álvarez-Ríos, Ana Isabel; Herrera-Hidalgo, Laura; Domínguez, Montserrat; Lozano, Carmen; Romero-Vazquez, Gloria; Roca, Cristina; Espinosa, Nuria; et al.
Abstract: Objectives: To evaluate whether simplification of antiretroviral treatment to dual therapy (DT) negatively impacts immune recovery (IR), immune activation and inflammation (IA/I), and HIV reservoir. Methods: An open-label, single-centre, randomized controlled trial conducted in adult virologically suppressed HIV-infected patients on triple therapy (TT) with elvitegravir-cobicistat, emtricitabine and tenofovir alafenamide or dolutegravir (DTG), abacavir, and lamivudine (3TC). Participants were randomized to continue TT or switch to DTG, or darunavir/cobicistat (DRVc) plus 3TC. IR was assessed by CD4 + /CD8 + ratio at 48 and 96 weeks. Changes in immune activation, proliferation, exhaustion, senescence, and apoptosis in CD4 + and CD8 + T cells, plasma sCD14, hsCRP, D-dimers, β2-microglobulin, IL-6, TNF-α and IP-10 levels, cell-associated HIV-DNA (CA-DNA), and unspliced HIV-RNA (usRNA) were also analysed. Results: One hundred and fifty-one participants were enrolled. Fourteen patients did not complete the follow up. In the ITT and PP analysis, the IR was similar between the treatment arms. In the ITT analysis, the median increase in CD4 + /CD8 + ratio was 0.10, 0.04, and 0.07 at week 48, and 0.09, 0.05, and 0.08 at week 96 for TT, DTG/3TC, and DRVc/3TC, respectively. After adjusting for confounding factors, the slopes of changes in CD4 + /CD8 + ratio over time were independent of treatment (F = 1.699; p = 0.436) and related only to baseline values (F = 756.871; p = 0.000). There were no differences in IA/I, CA-DNA, or usRNA between treatment arms. Discussion: Both IR and IA/I, CA-DNA, and usRNA were similar in the three treatment groups, regardless of maintaining TT or simplifying to DTG/3TC or DRVc/3TC in virologically suppressed HIV-infected patients. Graphical abstract: Image 1